Postcompetition blood lactate measurements and swimming performance: Illustrated by data from a 400-m Olympic record holder - Chatard, J. C.; Paulin, M.; Lacour, J. R. (Swimming Science V, 1988)
One of the most important problems in swimming competition is to know whether the swimmers' efforts are maximal or not, essential information for coaches and swimmers. To answer this question in other sports, one measure utilized has been the postcompetition blood lactate concentration (L). Keul, Kindermann, and Simon (1978) showed that in running, a maximal exercise was characterized by an L higher than 20 mM. Swimming is a rather different sport because it concerns a larger muscle mass. Specific references to swimming are thus needed to establish the relationship between L and performance level. Sawka, Knowlton, Miles, and Critz (1979) began to investigate L in freestyle swims over distances of 50 to 1,000 yd and in the 200-yd individual medley, butterfly, breast-, and backstrokes. The aim of the present study was to systematically document the maximal concentration of blood lactate (L max) measured at the end of competitions over 50 to 1,500 m in all the strokes. Among the same swimmers, some comparisons were made between different distances and strokes in order to investigate the possible effects of motivation and specific training programs. The L results measured on Thomas Fahrner (TF) during the 1983-84 Olympic season were used as an individual illustration of the general trends derived from these data.